(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The aim of the current study lies in showing and demonstrating the effect of the independent variable of organizational integrity with its dimensions represented by (organizational optimism, organizational trust, organizational integrity, organizational sympathy) on the dependent variable of strategic drifts through its dimensions represented by (organizational culture, leadership, innovation, strategic planning) .The analytical descriptive approach has been adopted and the questionnaire has been used as a tool to obtain data and information from the sample of (57) people who are at the administrative levels (senior management, middle management, executive management) in the researched company, and financial reports and statements for the years (20172021) have been relied upon in the interpretation of the results, in addition to conducting personal interviews with those responsible for it. Data has been analyzed based on the one statistical program (SPSS V.28) in calculating the (weighted arithmetic mean, standard drifts, coefficient of variation, percentage weight, regression coefficient, t-test, determination coefficient R, F-test, simple linear regression equation, confirmatory factor analysis). The current study has reached a set of results, the most prominent of which are: There is a significant effect of organizational integrity on strategic deviations, as well as the presence of significant differences in the sample’s response to organizational integrity and strategic drift together according to personal variables: gender, age, academic qualification, job position, number of years of service